ANALISIS SPEKTRUM GETARAN UNTUK MENGIDENTIFIKASISINYAL KONTAK GIGIDALAM SISTEM TRANSMISIRODA GIGI DIFFERENSIAL DENGAN MEMANFAATKAN CREATIVE SOUNDBLASTER AUDIGY LS 5.1 DAN MATLAB 6.5 - Eddy, Noor; Husen, A.; Kurniawan, Heru (MESIN, 2006)
Usually, a modern industry requires theproduction keep going on with the least interrupt as possible,butfrequently, the unscheduled maintenance will waste money in a large amount which is allocated in amodern industry needs an enormous investment. Machines with good condition generally produce a littlerelative of vibration but with increase in service life, the vibration of machine will increase. In somecondition, the increase in quite drastic vibration probablymay occur. Thisphenomenon is an indicator thatthe machine must have an immediate repair. This vibration spectrum analysis is tried to conductedfor thetransmission system of differential gear. By means to use the alternative tools beside DSA (Dynamic SignalAnalyzer), that is CREATIVE SOUNDBLASTER AUDIGY LS5.1 and MATLAB 6.5 whichhave Fast FourierTransform facility and so, can to know the real condition gear by time domain andfrequency domain. Thevibration spectrum analysiswhich donetofocus byidentification signal ofproblem which comebygear meshlikegear meshfrequency ofhypoidgear andside gear.